2005
DOI: 10.1590/s1678-77572005000300019
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dental caries and socio-economic factors in adolescents

Abstract: Dental caries has a multifactorial etiology, including socio-economic variables and access to dental care, which were discussed in the national survey conducted in 2002. The aim of this study was to investigate the socio-economic aspects and access to dental care, associated with caries prevalence and severity in adolescents from the State of São Paulo. The study design was cross-sectional, on which data on 1,825 adolescents aged 15 to 19 years achieved from the data of an epidemiological survey conducted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 13 publications
(7 reference statements)
4
10
1
8
Order By: Relevance
“…Adolescents from families with lower socioeconomic status had approximately 50% more dental caries experience than those from families with higher socioeconomic status. This result is consistent with previous studies and highlights the impact of social determinants in the development of oral diseases. The association between socioeconomic status and dental caries can also reinforce the results related to SOC.…”
Section: Discussionsupporting
confidence: 94%
“…Adolescents from families with lower socioeconomic status had approximately 50% more dental caries experience than those from families with higher socioeconomic status. This result is consistent with previous studies and highlights the impact of social determinants in the development of oral diseases. The association between socioeconomic status and dental caries can also reinforce the results related to SOC.…”
Section: Discussionsupporting
confidence: 94%
“…Sociodemographic factors related to dental caries, among other items, include schooling , household income , social class, and area of residence . In general, unfavorable sociodemographic status is related to a higher dental caries experience among children and adolescents . Indeed, children and adolescents who are growing up in poverty and social deprivation are at higher risk for dental caries .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified an association between oral health and socioeconomic variables such as family income 9,12,20 , educational level 12,22 , delay and disruption of the education of the child 7 and social class 16,23,33 , in various locations including Australia 17 , New Zealand 28 , Jordan 29 , Japan 31 , Sweden 19 , the UK 10 and Brazil 8,11,27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have addressed the correlation between oral health and social factors such as income, education, number of children, and other variables 12,16,21,22,25,31 . The national surveys conducted in Brazil in 2000 and 2010 showed that oral health is heterogenous, with differences found among regions and social groups.…”
Section: Introductionmentioning
confidence: 99%